Social and Environmental Contribution of Indonesian Baitul Maal wat Tamwil (BMT) to the SDGs Implementation - Aminudin Ma'ruf; Tilla Ira Sellani; Lukmanul Hakim; Shahbaz Alam (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to analyze the social and environmental contribution of Baitul Maal wat Tamwil (BMT) in Indonesia in supporting the implementation of SDGs in Indonesia. Theoretical framework: The underpinning theoretical framework of the study lies in the concept of Islamic economics with special reference to its social and environmental contributions. Literature review: The study's literature review provides the research development based on previous findings. It highlights the gap in the literature in the field of study, which needs to be addressed. Methods: The paper uses primary data that were obtained from in-depth interviews with 24 BMTs in several jurisdictions in Indonesia. A qualitative research method was used to explore and analyze BMTs' role thoroughly. Results: The results of this study inferred that BMTs in Indonesia have been actively contributing to society's social and environmental development. Their contributions are implemented through innovative programs tackling social and environmental issues. However, few BMTs contributed to one aspect but not the other and are expected to improve their contribution. This paper is unique from previous research with some recommendations and future implications. Implications: The study suggests some essential policy implications supporting the contributions of BMT in tackling the social and environmental issues in achieving the SDGs. Novelty: The research comes with new perspectives in the study of BMT towards SDGs implementation.